Selenium supplementation in pediatric patients using parenteral nutrition: Is it time to do something? - Freitas,Renata Germano Borges de Oliveira Nascimento (2018)
Summary Objective: To analyze the nutritional status of selenium and verify the effect of its supplementation in pediatric patients during 14 days of parenteral nutrition (PN). Method: This is a series of cases with patients followed for two weeks while using PN. Data collection was performed at the beginning (T0), in the 7th (T1) and 14th days of PN (T2). The supplemented group received 2 µg/kg/day of selenous acid. Weight and height were measured for nutritional status assessment. Tests requested: plasma selenium, albumin, pre-albumin, C-reactive protein (CRP), total cholesterol and HDL-cholesterol. Results: Fourteen (14) patients with inflammatory process and with low or very low weight for their ages were evaluated. In both groups (with and without supplementation), all patients had low selenium levels. Median plasma selenium concentrations were 17.4 µg/L (T0), 23.0 µg/L (T1) and 20.7 µg/L (T2). Increase and reduction of selenium occurred both in patients with high CRP and in those presenting normalization of this parameter. Conclusion: Lower plasma selenium levels have been detected since the start of the research and supplementation (2 µg/kg/day of selenous acid) was not to enough to approach the reference values.